Adoption of health care practices by smallholder farmers in cattle farming and the influencing socio-economic factors in Kelantan state, Malaysia - Amal Najim; S.M. Rezaul Karim; Amin, M. R. (2016)
The aim of this study was to find out the perception of smallholder farmers of Kelantan, Malaysia on health care practices in cattle farming and to explore the adoption of best health care practices done by them. The socio-economic factors of the farmers influencing adoption level were also studied. A stratified random sample of 240 cattle farmers of Kelantan was selected as the respondents of this study. A questionnaire including questions regarding eleven health care practices in cattle farming and socio-economic characteristics of the farmer were used as a tool for data collection during face-to-face interviews. Descriptive statistics including means, frequencies and percentages were used to determine the adoption levels. Correlation coefficients were estimated to determine the extent to which selected socio-economic characteristics influenced the adoption of health care practices. Prevalence of cattle disease in the study area was also recorded. Findings showed that their animals were infected mostly with “foot and mouth disease” (FMD) along with other diseases. The severity ranking of diseases in Kelantan is FMD<Brucellosis> anthrax > abortion>rinder pest. The adoption level in health care practices is low (mean score = 3.4) and it is influenced by the socio-economic variables of farmers e.g. farmers’ income (r = 0.005**) and farmers education level (r =0.0001**) had highly significant correlation at p< 0.01; farmers’ age (r = -0.0268*) and family size (r = -0.121*) had negative relationship at p<0.05; and types of breed they own (r = 0.247*), purpose of breeding cattle (r=0.143*), cattle farming as main occupation (r = 0.399*) and farmers’ sharing in training course (r=0.035*) had influenced positively at p<0.05 in following best health care practices. There was no influence of farm size, number of cattle and current knowledge in health care practices. The study also revealed that feeding calves during early stage and vaccination against foot and mouth disease are used by the farmers. Use of these information by the extension workers of the Kelantan state to improve their adoption level in health care practices have been emphasized.